Transformasi Hukum Perceraian dalam Sistem Hukum Islam dan Hukum Positif Indonesia: Analisis Maqāṣid al-Syarī‘ah terhadap Perlindungan Ketahanan Keluarga - Nabila Sabriana; Nurhayati Fadillah nurhayatifadillah965@gmail.com; Intan Nur 'Aini; Fachri Irwan Ibrahim Tarigan; Dea Alfiya Nurliza (Albayan Journal of Islam and Muslim Societies, 2026)
Divorce is a legal event that possesses complex religious, social, and juridical dimensions within Indonesian society. From the perspective of Islamic law, divorce is permissible as a last resort when marital life can no longer be maintained. Meanwhile, Indonesian positive law regards divorce as a legal act that must be conducted through judicial proceedings to ensure the protection of the rights of all parties involved. This study aims to analyze the transformation of the concept of divorce in Islamic law into the Indonesian national legal system and to examine its compatibility with the principles of maqāṣid al-sharī‘ah in protecting family resilience. This research employs a normative juridical method using statutory, conceptual, and maqāṣid al-sharī‘ah approaches. The legal materials consist of primary legal sources, including Law Number 1 of 1974 concerning Marriage as amended by Law Number 16 of 2019, the Compilation of Islamic Law, and other relevant regulations, as well as secondary legal materials such as books, scientific journals, and previous studies. The findings indicate that the Indonesian divorce system represents a transformation of Islamic law that prioritizes the protection of women’s and children’s rights through the judicialization of divorce. The requirement that divorce be conducted through the Religious Court does not contradict Islamic principles but rather reflects the implementation of maqāṣid al-sharī‘ah in protecting religion (ḥifẓ al-dīn), life (ḥifẓ al-nafs), lineage (ḥifẓ al-nasl), and property (ḥifẓ al-māl). Therefore, the Indonesian divorce system can be viewed as a form of Islamic legal reform oriented toward family protection and the realization of substantive justice.